Análise cinesiológica e biomecânica de atividades de manuseio de carga - Padula, Rosimeire Simprini (Universidade Federal de São Carlos, 2006)
Load handling activities impose great overloads on the musculoskeletal system, increasing the risk of injuries. The fact that these handling activities are considered risky had led to several studies regarding load lifting, lowering, pulling and pushing. The results obtained certainly allowed many findings about influence of different variables on risk factors of these activities. However, other studies are needed, especially about risks by load carrying activities, since the literature has not dealt extensively with this topic. Thus, studies have been carried out about load handling, leading to 4 scientific papers. Study one aimed at comparing two groups of workers, with and without musculoskeletal symptoms in the upper limbs when they performed simulated tasks of handling techniques as to trunk movements and load support. Movements analysis was quantified by a flexible electrogoniometer and contact between load and trunk, by load cells. Nine asymptomatic and 10 symptomatic industrial workers were evaluated. An ANOVA was performed to compare results between symptomatic and asymptomatic workers. Most of the symptomatic workers supported the load on their trunk, whilst most of the asymptomatic did not. Higher values of lumbar flexion occurred for the symptomatic workers (p<0,05). The objective of the second study was ti describe trunk movements in sedentary subjects, and in workers with and without musculoskeletal symptoms, when carrying loads in simulated tasks. The 38 subjects who participated in this study were divided into 4 groups, consisting of 9 male students, 10 female students, 10 female symptomatic industrial workers and 9 asymptomatic industrial workers. The trunk movements of all subjects were recorded by biaxial back electrogoniometer when carrying loads between surfaces of different heights. An analysis of variance for repeated measures were performed, which was followed by the Duncan post hoc test for comparison of anthropometrical data between subjects, amplitude of movement, and time spent in each movement per group and per experimental condition. The height of the surfaces to which the loads were carried to or from, significantly influenced the trunk positions during handling (p<0,01), as if subjects were anticipating the target position whilst handling. Also more time was spent in flexion (p<0,01) than in extension. These aspects increase the risks of possible injury in such activities. The objective of the third study was to describe the kinds of grip used during handling activities of 5Kgf and 10 Kgf loads between surfaces of different height and to quantify flexion/extension movements and wrist radial and ulnar deviations quantified by electrogoniometry. Ten male volunteers participated in this study handled a box between surfaces of different heights. The activities was performed to evaluate significant differences between the anthropometry of volunteers´ hands and between movements used for load handling and different heights. The results showed that the surface heights to which the objects were handled significantly influenced (p=0,000) joint amplitudes, nevertheless there wasn t any difference in the movements for different load masses handled (p=0,43). Time over what is considered advisable was spent in radial deviation when handling involved high surfaces. The fourth study aimed at evaluating the anterior-posterior movements of the trunk and the time spent in task performance by experienced and inexperienced subjects during load handling activities to different target surfaces. The 36 subjects who participated in this study were healthy males, divided into groups of 16 and 20, experienced and inexperience respectively, in the performance of load handling activities. The activities consisted of carrying the 7Kg and 15Kg boxes from a surface at a fixed height to another at a variable height. Lumbar thoracic movements were quantified by a flexible electrogoniometer. Significant differences were found in the time spent to perform the handling between the groups (p<0,008) and between the loads (p<0,000). However, there was no significant difference in the trunk movemets between the groups (p>0,005) and the loads (p>0,005). Surfaces heights to which the box was transported significantly influenced trunks movements (p<0,000).
Keywords: Fisioterapia preventiva; Biomecânica; Cinesiologia; Eletrogonometria; Manuseio de carga; Movimentos do tronco; Distúrbios músculo-esqueléticos; Preensão; Movimentos antecipatórios; Handling; Load carrying; Trunk movements; Musculoskeletal disorders; Grip; Electrogoniometer; Anticipatory movements; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL